IoT-based data security and protection for hospital information systems: A knowledge graph analysis - HOUNGUE, Yénukunmè Pélagie Elyse; OGA, David N.; SARR, Cheikh (My University, 2023)
Nowadays, the Internet of things (IoT) is applied in several domains such as health, domotic, transport, agriculture and so on. This research work proposes a knowledge graph analysis of hospital information systems applied to IoT. We used Dimensions base collection as a data source combined with VOSviewer software to establish different possible joins in order to bring out some relevant results. Thus, bibliometric methods for the analysis of 4743 articles published in the field of IoT security and data protection for hospital information systems have been provided. The results show that the field of IoT-based health research born from 2014 continues to grow. This study provides important knowledge support for further research. In the coming days, we will focus on the state of the art of IoT security and data protection for hospital information systems for remote and real-time patient monitoring.
Keywords: Data security and protection · Hospital information system · Graph analysis